Evaluation of the effect scan pattern has on the trueness and precision of six intraoral digital impression systems. Issue 2 (24th February 2018) - Mennito, Anthony S.; Evans, Zachary P.; Lauer, Abigail W.; Patel, Ravi B.; Ludlow, Mark E.; Renne, Walter G.
Abstract: Objective: Clinicians have been slow to adopt digital impression technologies due possibly to perceived technique sensitivities involved in data acquisition. This research has two aims: determine whether scan pattern and sequence affects the accuracy of the three‐dimensional (3D) model created from this digital impression and to compare the 5 imaging systems with regards to their scanning accuracy for sextant impressions. Materials and Methods: Six digital intraoral impression systems were used to scan a typodont sextant with optical properties similar to natural teeth. The impressions were taken using five different scan patterns and the resulting digital models were overlayed on a master digital model to determine the accuracy of each scanner performing each scan pattern. Furthermore, regardless of scan pattern, each digital impression system was evaluated for accuracy to the other systems in this same manner. Results: No differences of significance were noted in the accuracy of 3D models created using six distinct scan patterns with one exception involving the CEREC Omnicam. Planmeca Planscan was determined to be the truest scanner while 3Shape Trios was determined to be the most precise for sextant impression making. Conclusions: Scan pattern does not significantly affect the accuracy of the resulting digital model for sextant scanning. Clinical Significance: Companies who make digital impression systems often recommend a scan pattern specific for their system. However, every clinical scanning scenario is different and may require a different approach. Knowing how important scan pattern is with regards to accuracy would be helpful for guiding a growing number of practitioners who are utilizing this technology.